Effect of montmorillonite on flame spread characteristics and smoke toxicity of acrylonitrile butadiene styrene copolymer composite. Issue 4 (20th May 2016) - Ren, Xiaonan; Zong, Ruowen; Hu, Yuan; Lo, Siuming
Abstract : In this article, MMT (montmorillonite) and ABS (acrylonitrile butadiene styrene) blends were prepared via melt blending process using a twin‐screw extruder. Differences of flame spread characteristics and smoke toxicity with addition of MMT was analyzed. Flame spread properties of materials with different geometric dimension and the side covering degree were investigated with a high definition digital camera and image processing technology. Smoke toxicity under different ventilation condition were studied using a steady state tube furnace (BS 7900, ISO TS 19700). The addition of MMT remarkably reduced the flame spread rate of ABS especially for burning without sidewall. In well‐ventilated conditions, MMT increase the toxicity of the effluent by increasing the CO yield. In under‐ventilated conditions, the FED values of two materials were almost same. POLYM. COMPOS., 39:1234–1241, 2018. © 2016 Society of Plastics Engineers